2007
DOI: 10.1523/jneurosci.5094-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PAR-1 Kinase and Stimulation of Tau Phosphorylation by Diverse Signals Require the Tumor Suppressor Protein LKB1

Abstract: Aberrant phosphorylation of tau is associated with a number of neurodegenerative diseases, including Alzheimer's disease (AD). The molecular mechanisms by which tau phosphorylation is regulated under normal and disease conditions are not well understood. Microtubule affinity regulating kinase (MARK) and PAR-1 have been identified as physiological tau kinases, and aberrant phosphorylation of MARK/PAR-1 target sites in tau has been observed in AD patients and animal models. Here we show that phosphorylation of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
84
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 53 publications
4
84
0
Order By: Relevance
“…Future investigations should determine whether metabolic stress, environmental insults, or other pathological situations known to activate AMPK, could impact brain development through its ability to modulate axon formation, axon growth, and maybe other aspects of neuronal differentiation. Our results have important implications in the context of neurodegeneration especially in light of recent results suggesting that in Drosophila, neurodegeneration induced by Par1 (MARK)-mediated Tau-hyperphosphorylation can be significantly suppressed by reducing LKB1 expression (37,38). Future experiments should further explore the relationship between metabolic stress, AMPK activation, and axon formation, growth, or maintenance in the context of neurodegeneration.…”
Section: Discussionmentioning
confidence: 64%
“…Future investigations should determine whether metabolic stress, environmental insults, or other pathological situations known to activate AMPK, could impact brain development through its ability to modulate axon formation, axon growth, and maybe other aspects of neuronal differentiation. Our results have important implications in the context of neurodegeneration especially in light of recent results suggesting that in Drosophila, neurodegeneration induced by Par1 (MARK)-mediated Tau-hyperphosphorylation can be significantly suppressed by reducing LKB1 expression (37,38). Future experiments should further explore the relationship between metabolic stress, AMPK activation, and axon formation, growth, or maintenance in the context of neurodegeneration.…”
Section: Discussionmentioning
confidence: 64%
“…Analogously, NUAK1, also known as AMPKrelated protein kinase 5, was the downstream molecule of Akt, which participated in the classical signaling pathway with extensive consequences [63]. Numerous studies have confirmed that Akt-ARK5 was closely related to cancer development and metastasis through blocking cell apoptosis by the inhibition of caspase 8 activation [64,65].…”
Section: +mentioning
confidence: 99%
“…These data are consistent with a functional role for the UBA domains in stabilizing an open conformation of the N-and C-terminal lobes of the kinase domain through interactions with the N-lobe (as observed in the kinase:UBA domain crystal structures), which in turn exposes the kinase domain activation segment for phosphorylation by LKB1/Par4. LKB1/Par4-mediated phosphorylation of the Par1/MARK activation segment threonine increases kinase activity Ͼ50-fold in vitro (36) and activates Drosophila Par1 in vivo (37).…”
Section: Conformational Instability Modifies the Ligand-binding Propementioning
confidence: 99%